Pathogenic and cultural variability among Indian isolates of Fusarium oxysporum f.sp. lycopersici causing wilt in tomato - R.C. GUPTA*, K.K. PANDEY and (Indian Phytopathology, 2014)
Fusarium wilt caused by Fusarium oxysporum f.sp. lycopersici is a destructive disease of tomato in India. The present study was carried out to characterize different isolates of F. oxysporum f.sp. lycopersici collected from seventeen states in the country on the basis of virulence and colony characters. A total of ninety-five isolates were classified in four virulence grade highly virulent (10), virulent (60) and moderately virulent (25). The pigmentation of culture on PDA medium was grouped in five categories and varied from creamy white to blackish red where majority of the isolates (24) come under light pink. Based on the radial growth, the isolates were categorized in three groups as fast growing (›70 mm), moderate growing (51-70 mm) and slow growing (‹50 mm) after nine days of incubation. The present study revealed that, at least three different physiological variants exist in the collected isolates of F. oxysporum f.sp. lycopersici in the country.